If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x) + ln(7x) = -3 Multiply ln * x lnx + ln(7x) = -3 Remove parenthesis around (7x) lnx + ln * 7x = -3 Reorder the terms for easier multiplication: lnx + 7ln * x = -3 Multiply ln * x lnx + 7lnx = -3 Combine like terms: lnx + 7lnx = 8lnx 8lnx = -3 Solving 8lnx = -3 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Divide each side by '8nx'. l = -0.375n-1x-1 Simplifying l = -0.375n-1x-1
| -9-13x=199 | | 2ax+2by=118 | | 1(x+5)=0 | | ln(x)+kn(7x)=-3 | | -18x=x+22 | | 5x+9-2x=1+3x+8 | | 13=y-5x | | 8(2+r)=-200 | | 60=x+x+7+2+2x-7 | | 47-3k=10(-6+10k)+4k | | 3p-10=63 | | 2cos^2x=5+5sinx | | 4=v+-2 | | 1/4+x=-7/2 | | (-5x)1=12x(1) | | y+.07y=175 | | 7-c=-20 | | (9x-6)=(8.5x+2) | | -3.2=t+0.2 | | 5n-18=-128 | | 5a-1(8-a)=4a-10 | | 13y+37=89 | | -4a+2+5a=10-19 | | 333=-14x-3 | | 6x-12+8x-10=180 | | 9x+0.7=54.7 | | -7/9x=-6*9x | | -7+6x=-19 | | 7+1.50=29.50 | | 6a+11=2a+82 | | -15+9b=-8(2b-3) | | 91=-5d+6 |